Palliative care for cirrhosis: a UK survey of health professionals' perceptions, current practice and future needs. Issue 1 (24th July 2015) - Low, Joseph; Vickerstaff, Victoria; Davis, Sarah; Bichard, Julia; Greenslade, Lynda; Hopkins, Katherine; Marshall, Aileen; Thorburn, Douglas; Jones, Louise
Abstract : Objective: To determine the knowledge and practice patterns of a UK cohort of relevant healthcare professionals (HCPs) about delivering palliative care in cirrhosis, and to inform priorities for future research. Design: An on-line questionnaire survey with closed and open responses. Setting: HCPs identified from the mailing list of special interest groups in hepatology and gastroenterology (liver), general practice and specialist palliative care (SPC) across the UK. Results: Of the 6181 potential contacts identified, 517 HCPs responded. Most believed a role exists for SPC in caring for people with cirrhosis, but many SPC HCPs felt ill prepared to provide good care to those facing death. Further training was needed in managing liver-related symptoms, symptom control and end of life issues. All HCP groups wished to increase community provision of palliative care support, but many general practitioners felt unable to manage advanced cirrhosis in the community. There were differences in the optimal trigger for SPC referral with liver HCPs less likely to refer at symptom deterioration. Prognostication, symptom management and service configuration were key areas identified for future research. Conclusions: All who responded acknowledged the role of SPC in caring for those dying with cirrhosis and need for further training to improve confidence and enable joint working between SPC, general practice and liver teams. Low response rates make it difficult to generalise these findings, which require further validation.